Information Model of LibMeta Digital Library - Ataeva, O. M.; Serebryakov, V. A. (Lobachevskii journal of mathematics, 2019)
When developing a digital library, heavy emphasis is laid onto the library information model. The content of digital libraries can be featured in different formats and presented in different ways. The library, as defined by the LibMeta system, is a storage of structured and diverse data with the possibility of integrating it with other data sources and specifying its content by analysing the subject area. The semantic content ontology of the library provides basis for further content formalization. The article introduces the basic concepts needed to describe the problem of data integration, as well as concepts required for the definition of an unspecified thesaurus. The ontology’s structure enables the possibility to determine the semantic library within any subject area.